Yo Cayetana: The Woman in Her Own Words - Birrento, Ana Clara; Saianda, Maria Helena; Goncalves, Olga M. (European Scientific Journal, ESJ, 2017)
Much has been said and written about Cayetana de Alba, â€œGrandee of Spainâ€ and a woman who took an important part in some of the historical moments of her lifetime. The images the media conveyed of her â€“ that of a frivolous woman - is, yet, contradicted by her autobiography. The aim of this paper is, therefore, to investigate Cayetanaâ€™s discursive gendered positions from an interdisciplinary standpoint: based on a lexicometric approach of the data collected, the semio-linguistic interpretation highlights the possibilities and modalities of her Self represented in images and emotions involved in the real world and in a historical conjuncture in which the present and the past are articulated. Her words enable us to understand the strategies she uses to construct her identity and her own meanings in the representation of her lived experience in the interstices of the Self and of social relations (Probyn, 1993).